2023
DOI: 10.1111/srt.13300
|View full text |Cite
|
Sign up to set email alerts
|

Study about evaluation of efficacy of methotrexate in localized scleroderma using ultrasonography

Abstract: Background:The treatment and curative effect evaluation of localized scleroderma (LS) still perplexes many clinical workers.Purpose: To investigate the efficiacy of methotrexate in the treatment of LS by the evaluation of ultrasonography. Methods: A prospective study enrolled 10 patients treated with MTX for at least 6 months was conducted. Treatment outcome was evaluated by a clinical score and 15-MHz ultrasonography. Safety assessment included the monitoring of adverse drug reactions and clinical laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…On longitudinal assessments with US, they found a significant decrease in DT with the average decrease being 69% [ Figure 2 ]. [ 10 ] Although no statistical difference existed between the clinical scoring systems and US measurements, the US measurements were more sensitive as the changes could be detected earlier in response to the treatment with the average first reaction time being 1.8 months. This provides further evidence for the utility of US as a tool to assess therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…On longitudinal assessments with US, they found a significant decrease in DT with the average decrease being 69% [ Figure 2 ]. [ 10 ] Although no statistical difference existed between the clinical scoring systems and US measurements, the US measurements were more sensitive as the changes could be detected earlier in response to the treatment with the average first reaction time being 1.8 months. This provides further evidence for the utility of US as a tool to assess therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Chen et al, 8 compared the skin thickness measurement by US with the skin biopsy and reported good agreement in patients with scleroderma. Furthermore, Zhang et al 9 Reported the usefulness of US in skin evaluation after treatment with methotrexate in localized scleroderma. There are multiple therapeutic options for morphea.…”
Section: Introductionmentioning
confidence: 99%